PENGARUH METODE BABY LED WEANING TERHADAP KETERAMPILAN ORAL MOTOR PADA BAYI (6-12 BULAN) DI KLINIK PRATAMA TANJUNG KECAMATAN DELI TUA - Sari, Husna; Hayati, Erlina; Siregar, G.F. Gustina (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
The Baby Led Weaning method is a method of eating activities that introduces healthy family foods that are often consumed by families in the form of finger food and gives children the opportunity to eat on their own since the beginning of the process of introducing complementary foods to breast milk. Breast milk only meets the nutritional needs of infants as much as 60% in infants aged 6-12 months. The rest must be met with other foods that are sufficient in number and good in nutrition. Therefore, at the age of 6 months and over, babies need additional nutrition from complementary foods, but the MP-ASI given must also be of high quality. Objective: To determine the effect of the Baby Led Weaning Method on Oral Motor Skills in Infants (6 – 12 months). Methods: This type of research is pre-experimental with a One Group Prestest-Posttest design. This sampling uses a total sampling and obtained 15 infants 6-12 months. Conclusion: This study uses the Wilcoxon test. Based on the results of bivariate analysis using the Wilcoxon test, p-value of 0.001 < 0.05 means that Ho is rejected and Ha is accepted, which means that it can be said that there is an effect of giving the baby lad weaning method on oral motor skills in infants. -12 months at Tanjung Pratama Clinic.